If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.16 + -0.01(x + 2) = -0.02(2 + -1x) Reorder the terms: 0.16 + -0.01(2 + x) = -0.02(2 + -1x) 0.16 + (2 * -0.01 + x * -0.01) = -0.02(2 + -1x) 0.16 + (-0.02 + -0.01x) = -0.02(2 + -1x) Combine like terms: 0.16 + -0.02 = 0.14 0.14 + -0.01x = -0.02(2 + -1x) 0.14 + -0.01x = (2 * -0.02 + -1x * -0.02) 0.14 + -0.01x = (-0.04 + 0.02x) Solving 0.14 + -0.01x = -0.04 + 0.02x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.02x' to each side of the equation. 0.14 + -0.01x + -0.02x = -0.04 + 0.02x + -0.02x Combine like terms: -0.01x + -0.02x = -0.03x 0.14 + -0.03x = -0.04 + 0.02x + -0.02x Combine like terms: 0.02x + -0.02x = 0.00 0.14 + -0.03x = -0.04 + 0.00 0.14 + -0.03x = -0.04 Add '-0.14' to each side of the equation. 0.14 + -0.14 + -0.03x = -0.04 + -0.14 Combine like terms: 0.14 + -0.14 = 0.00 0.00 + -0.03x = -0.04 + -0.14 -0.03x = -0.04 + -0.14 Combine like terms: -0.04 + -0.14 = -0.18 -0.03x = -0.18 Divide each side by '-0.03'. x = 6 Simplifying x = 6
| 3xy(5xy)+3xy(1)=equation | | 17x-3-12=.2(25x-10) | | 3xy(5xy)+3xy(1)= | | 16t^2+150t+20=0 | | 5x+2=36 | | .5x-.625=.75x+.375 | | 2x(x-4)+x(3-2x)= | | 13r+4-7r= | | -2+ln(x-4)=4 | | 5x+10x+5=25 | | 5x+10x+5=25 | | 5x+10x+5=25 | | 2B-6=4B | | 3-(3x-8)=4y-5 | | (4c-6c+5)(4c-2c-1)= | | lnx-2lnx=3 | | 6x-4=20x+3 | | 6x-23+x+54=180 | | 4x+2x(x+4)= | | -4x-6(-2+4)=64 | | 2x+y-z=7z | | -4x-6(-2+4)=64 | | 3x-1=-3x+3 | | 3x-1=-3x+3 | | -5x+-2=-2X+4 | | -6x-5(-3x-3)=60 | | 114=2x+3x | | 5x+7y=3890 | | 8x+7y-5-5x+6y-3= | | -2x-2(-5x-4)=-80 | | 15+4y-1=15y-13-2y | | y+(y-2)2=2 |